Novel Anodic TiO2 Synthesis Method with Embedded Graphene Quantum Dots for Improved Photocatalytic Activity - Knoks, Ainars; Grinberga, Liga; Kleperis, Janis (MDPI, 2024)
Photocatalytic degradation of pollutants have a high potential for sustainable and renewable uses. TiO2 is a widely studied photocatalyst due to its high chemical and photochemical stability and wide range of applications. However, the wide band gap and low capacity of photo-induced charge separation provide lower catalytic activity; thus, improvement of these properties must be found. The doping of TiO2 with other elements, such as carbon nanoparticles (CNP) in a quantum dot form, offers a promising pathway to improve the aforementioned properties. In addition, in situ doping methods should be investigated for practical scalability, as they offer the advantage of integrating dopants directly during material synthesis, ensuring a more uniform distribution and better interaction between the dopant and the host material, in turn leading to more consistent photocatalytic properties. Current technologies primarily involve nanoparticle combinations. This work focuses on the development of a novel in situ synthesis methodology by the introduction of three different graphene-based quantum nanodots into anodic TiO2 and the following investigation of structural, morphological, and photocatalytic properties. Results indicate that the introduction of CNP allows for the shift of a set of parameters, such as the optical band gap, increased photo-induced charge carrier density of TiO2/CNP composite, and, most importantly, the change of crystalline phase composition depending on added CNP material. Research indicates that not only a higher concentration of added CNP enhances higher photocatalytic activity as tested by the degradation of methylene blue dye, but also the type of CNP determines final crystalline phase. For the first time brookite and rutile phases were obtained in anodic titania synthesized in inorganic electrolyte by introducing hydrothermally treated exfoliated graphene. © 2024 by the authors. --//-- This is an open-access article Knoks, A.; Grinberga, L.; Kleperis, J. Novel Anodic TiO2 Synthesis Method with Embedded Graphene Quantum Dots for Improved Photocatalytic Activity. Coatings 2024, 14, 1407. https://doi.org/10.3390/coatings14111407 published under the CC BY 4.0 licence.
The research is funded by the Latvian Council of Science (project "Smart materials, photonics, technology and engineering ecosystem", project No. VPP-EM-FOTONIKA-2022/1-0001), Institute of Solid State Physics, University of Latvia, as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. Materials were funded by Scientific Research Project for Students and Young Researchers Nr. SJZ/2018/9 realized at the Institute of Solid State Physics, University of Latvia.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; anodic TiO2; carbon nanoparticles; composite; doped TiO2; photocatalysis